Technology Personalities in the Classroom: A New Classification System of TechTypes from Expert to Techy Turtle - Julie H. Oestreich; Jason W. Guy (MDPI AG, 2023)
The incorporation of technology in higher education has increased rapidly in recent years to allow for remote work and to promote active learning. Technology use could align with personality type and adopter status as defined by the diffusion of innovations theory. A review of the literature was conducted using PubMed with 106 articles found, and 2 articles meeting the inclusion criteria of the study. Search terms included "technology AND education", "pharmacy AND personality", "technology AND faculty AND personality", and "technology AND health educators AND personality". This paper highlights the current literature and introduces a new classification system to describe the technology personalities of instructors. The proposed personality types (TechTypes) include expert, budding guru, adventurer, cautious optimist, and techy turtle. Awareness of the advantages and disadvantages of each personality type-as well as one's own technology personality-may guide the selection of collaborators and tailor technology training for future growth.